X-Ray radiography of Ti6Al4V welded by Plasma Tungsten Arc (PTA) welding - Dikbas, Halil; Caligulu, Ugur; Taskin, Mustafa; Turkmen, Mustafa (Carl Hanser Verlag, 2013)
In this study, X-ray radiographic tests of Ti6A14V alloys welded by plasma tungsten arc welding (PTA) were investigated. PTA welding experiments were carried out under argon shielding gas atmosphere, at 1400-1600 W and 1800 W welding powers as well as 1 m/min, 0.75 m/min, and 0.50 m/min welding speeds. After this process, radiography of the welded joints was performed by X-ray diffraction. The result of the radiographic tests indicated that by increasing welding power the widths of deep penetration increased in all specimens. On the contrary, increasing welding speeds decreases the widths deep penetration. The best properties of Ti6A14V joints were observed for specimens welded at 1800 W welding power and at 0.50 m/min welding speed. © Carl Hanser Verlag, München.
Keywords: Argon; Electric welding; Nondestructive examination; Titanium alloys; Tungsten; Welding; X ray diffraction; Deep penetration; Radiographic test; Shielding gas; Ti-6al-4v; Ti6A14V alloy; Tungsten arc welding; Welding power; Welding speed; X ray radiography